Self-Bondable and Stretchable Conductive Composite Fibers with Spatially Controlled Percolated Ag Nanoparticle Networks: Novel Integration Strategy for Wearable Electronics - Kwon, Chaebeen; Seong, Duhwan; Ha, Jeongdae; Chun, Dongwon; Bae, Jee Hwan; Yoon, Kukro; Lee, Minkyu; Woo, Janghoon; Won, Chihyeong; Lee, Seungmin; Mei, Yongfeng; Jang, Kyung-In; et al. (WILEY-V C H VERLAG GMBH, 2020)
Advances in electronic textiles (E-textiles) for next-generation wearable electronics have originated from making a balance between electrical and mechanical properties of stretchy conductive fibers. Despite such progress, the trade-off issue is still a challenge when individual fibers are woven and/or stretched undesirably. Time-consuming fiber weaving has limited practical uses in scalable E-textiles. Here, a facile method is presented to fabricate ultra-stretchable Ag nanoparticles (AgNPs)/polyurethane (PU) hybrid conductive fibers by modulating solvent diffusion accompanied by in situ chemical reduction and adopting a tough self-healing polymer (T-SHP) as an encapsulation layer. First, the controlled diffusivity determines how formation of AgNPs is spatially distributed inside the fiber. Specifically, when a solvent with large molecular weight is used, the percolated AgNP networks exhibit the highest conductivity (30 485 S cm(-1)) even at 300% tensile strain and durable stretching cyclic performance without severe cracks by virtue of the efficient strain energy dissipation of T-SHP encapsulation layers. The self-bondable properties of T-SHP encapsulated fibers enables self-weavable interconnects. Using the new integration, mechanical and electrical durability of the self-bonded fiber interconnects are demonstrated while stretching biaxially. Furthermore, the self-bonding assembly is further visualized via fabrication of a complex structured E-textile.